Hubungan Kualitas Pelayanan Antenatal Care (ANC) dengan Tingkat Kepuasan Ibu Hamil: Literatur Review - Muliatul Jannah; Atika Zahria Arisanti; Jenitha Distya Putri Annisa (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Maternal Mortality Rate (MMR) is a common problem in maternal and child health in Indonesia. Therefore, Antenatal care (ANC) is one of the right ways to accelerate the reduction in MMR so that a healthy pregnancy can be achieved, a safe birth, and the birth of a healthy, quality baby. To be able to provide an overview of the quality of service provided by health care facilities to patients, it is very necessary for medical personnel and institutions to pay attention to patient satisfaction. To analyze the relationship between the quality of antenatal care services and the level of satisfaction of pregnant women in relation to several previous studies by examining and reviewing several selected studies. This literature review is a collection of research that uses research data collection techniques whose research subjects come from various library sources. The review sources used in this literature come from Pubmed and Google Scholar which were taken over a period of the last 5 years, starting from 2019-2023. From the 15 scientific articles analyzed, it was found that overall there was a relationship between the quality of ANC services and the satisfaction of pregnant women. However, there are differences between some articles regarding whether or not there is a relationship between aspects of reliability and assurance and pregnant women's satisfaction with the quality of ANC services.